2016
DOI: 10.1007/s12529-016-9552-0
|View full text |Cite
|
Sign up to set email alerts
|

The Clustering of Lifestyle Behaviours in New Zealand and their Relationship with Optimal Wellbeing

Abstract: Multiple lifestyle behaviours were positively associated with optimal wellbeing. The results show lifestyle behaviours cluster, providing support for multiple behaviour lifestyle-based interventions for optimising wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…Consistent with previous research, the findings of this study confirmed that health behaviors cluster together at both ends of the risk spectrum. 19,23,30 13,24 Furthermore, both classes with high-risk daytime behaviors were characterized by participants who were younger, non-university educated, did not have a partner, worked longer hours and had a lower annual household income than those in the low-risk classes. 60 61,62 A…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous research, the findings of this study confirmed that health behaviors cluster together at both ends of the risk spectrum. 19,23,30 13,24 Furthermore, both classes with high-risk daytime behaviors were characterized by participants who were younger, non-university educated, did not have a partner, worked longer hours and had a lower annual household income than those in the low-risk classes. 60 61,62 A…”
Section: Discussionmentioning
confidence: 99%
“…28,29 But these behaviors have received less research attention than other health behaviors such as smoking and alcohol consumption. Poor sleep and prolonged sitting co-occur with other health behaviors 30 and have been associated with worse health-related quality of life 13 . Poor mental health is also strongly associated with high-risk health behaviors 31 and morbidity [32][33][34] , and furthermore, depression and anxiety disorders have a stronger associations with decreased health-related quality of life than medical risk factors like cardiovascular disease, hypertension, arthritis, or medical injury 35 .…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with studies showing clustering of unhealthy, but also healthy, behaviours ( 23 ) . Recently, a study in 9425 New Zealand adults demonstrated a two-level clustering of fruit and vegetable intake with physical activity, sedentary behaviour and SSB consumption: optimal wellbeing was higher in healthy behaviour combinations ( 24 ) . In our study, young age was associated with higher added sugar intakes – a phenomenon seen in other cultures as well ( 25 – 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Wellbeing has been extensively researched as an indicator of quality of and satisfaction with life and optimal functioning, and it has been associated with both physical and mental health ( Ryan and Deci, 2001 ; Chanfreau et al, 2008 ; Davoren et al, 2013 ; Prendergast et al, 2016 ). In the general population ( Booker and Sacker, 2011 ; Davoren et al, 2013 ; Office for National Statistics, 2016 ), studies have shown that women tend to score lower on wellbeing than men, a pattern that has not yet been fully explained.…”
Section: Introductionmentioning
confidence: 99%